RETRACTED ARTICLE: Novel magnetic organic–inorganic hybrids based on aromatic polyamides and ZnFe2O4 nanoparticles with biological activity - Reza Eivazzadeh-Keihan; Mostafa Ghafori Gorab; Hooman Aghamirza Moghim Aliabadi; Mohammad mahdavi; Ali Reza Akbarzadeh; Ali Maleki; Hossein Ghafuri (Scientific Reports)
Abstract Magnetic nanoparticles were creatively selected as stable, inexpensive, biodegradable, facile recoverable, and functionalizable supports for a variety of synthetic and natural polymers. Herein, for the first time, aromatic polyamide was synthesized on the magnetic core of zinc iron oxide (ZnFe2O4). Terephthaloyl chloride and derivations of phenylenediamine were employed as monomers in this polymerization process. The toxicity of the synthesized hybrid at the highest concentration (1000 μg/ml) is 13.65% and on the other hand, the cell viability percentage is 86.35%. So, the prepared hybrid is biocompatible and non-toxic to Hu02 cells. Also, it has antibacterial ability against gram-positive and gram-negative bacteria. Because the results show that the minimum inhibitory concentration (MIC) of the synthesized polymer for bacteria such as Staphylococcus aureus ATCC 25923, Escherichia coli ATCC 25922, and Pseudomonas aeruginosa ATCC 27853 is in the range of 500–1000 µg/ml. Moreover, the hemolytic effect of ZnFe2O4 based hybrid was below 9% at the concentration of 1000 μg/ml. Therefore, it is compatible with red blood cells.